2009
DOI: 10.1002/dc.21224
|View full text |Cite
|
Sign up to set email alerts
|

Oral epithelial atypical changes in apparently healthy oral mucosa exposed to smoking, alcohol, peppers and hot meals, using the AgNOR and Papanicolaou staining techniques

Abstract: To evaluate cytological atypical changes in apparently healthy oral mucosa exposed to smoking, alcohol, hot meals, and peppers using the AgNOR and Papanicolaou methods. A total of 180 individuals were evaluated, of which 60 were smokers, 34 were alcohol users, 52 were habitual peppers and hot meal (exposed) consumers, 24 were non-exposed, and 10 were patients with Oral Squamous Cell Carcinoma (OSCC), as an internal control. Cytological materials were obtained by brushing of buccal mucosa, on the border of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…Several reports have indicated that tobacco smoking can result in oral precancerous lesions, which can gradually progress into oral cancer, even in the absence of clinical indicators. In the evolution of malignant progression, changes happen at the cellular level before clinical changes become evident [20,21]. Thus, detection of high-risk precancerous oral lesions and intervention is a major key toward reducing the incidence, prevalence, death and cost of treatment associated with oral cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have indicated that tobacco smoking can result in oral precancerous lesions, which can gradually progress into oral cancer, even in the absence of clinical indicators. In the evolution of malignant progression, changes happen at the cellular level before clinical changes become evident [20,21]. Thus, detection of high-risk precancerous oral lesions and intervention is a major key toward reducing the incidence, prevalence, death and cost of treatment associated with oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, detection of high-risk precancerous oral lesions and intervention is a major key toward reducing the incidence, prevalence, death and cost of treatment associated with oral cancer. Early alterations in the oral mucosa can be identified oral exfoliative cytology through screening of population at risk [15][16][17][18][19][20][21][22][23]. Oral Exfoliative Cytology is well accepted by patients and it is a practical diagnostic and screening method for diagnosis and early detection of oral mucosal lesions [24].…”
Section: Discussionmentioning
confidence: 99%
“…The major etiologic factors in the development of oral cancer is tobacco use and alcohol consumption. 10,19 The identification of prognostic and predictive markers is clinically essential, since oral cancer is a group of heterogenous diseases with different biological and clinical features. The current study point out the utility of PTEN in the genesis of carcinoma of oral.…”
mentioning
confidence: 99%
“…Its potential in identifying precancerous and cancerous lesions in the buccal mucosa smears has also been explored [15]. Ever since tobacco has been identified as an etiologic factor for oral cancer, numerous studies have also been done on tobacco smokers’ mucosa using AgNORs to evaluate early changes in their mucosa showing positive results [16,17,18,19,20,21,22,23,24,25,26,27]. …”
Section: Introductionmentioning
confidence: 99%
“…Though several studies exist using PAP and AgNOR together among tobacco smokers [17,20,22,24], there is none that has evaluated these parameters among quid chewers. The purpose of the present study is to assess cellular proliferation levels and cytological atypia in quid chewers and non-chewers using AgNOR and PAP techniques, respectively.…”
Section: Introductionmentioning
confidence: 99%